2015
DOI: 10.14742/ajet.1311
|View full text |Cite
|
Sign up to set email alerts
|

Social support as a neglected e-learning motivator affecting trainee’s decisions of continuous intentions of usage

Abstract: <p>Drawing from the social influence theory and acknowledging that the others’ support within the work context affects employees’ learning, values, and behaviours, an alternative framework was proposed to explain employees’ learning satisfaction and future intention to participate in e-training programs in the current study. 578 survey data collected from employees of various corporations in Taiwan provide empirical support for our extended model. The results suggest that social support from peers and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
53
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(78 citation statements)
references
References 53 publications
18
53
0
1
Order By: Relevance
“…For example, both peer and family support were significant antecedents of the behavioral intention to accept Facebook. These findings also corroborated previous research into the influence of social support on trainees' decisions to use e-learning systems (Weng et al, 2015). A rational explanation for such outcomes could be that the users' behavioral intention to use an SNS (Facebook) was directly affected by their social environment, where shared ideas, general comments, and positive encouragement all motivated them to perform a certain behavior.…”
Section: Social Support Theory and The Integrated Conceptual Modelsupporting
confidence: 85%
See 3 more Smart Citations
“…For example, both peer and family support were significant antecedents of the behavioral intention to accept Facebook. These findings also corroborated previous research into the influence of social support on trainees' decisions to use e-learning systems (Weng et al, 2015). A rational explanation for such outcomes could be that the users' behavioral intention to use an SNS (Facebook) was directly affected by their social environment, where shared ideas, general comments, and positive encouragement all motivated them to perform a certain behavior.…”
Section: Social Support Theory and The Integrated Conceptual Modelsupporting
confidence: 85%
“…To the best of the author's current knowledge, this area of research has not yet been studied. In line with our assumption, Weng et al (2015) found that family support was a predictor of the behavioral intention to adopt a Web-based learning system, whereas peer support was not. Hence, this study suggests the following hypotheses, in light of the nature of the proposed relationships:…”
Section: Social Support Theorysupporting
confidence: 85%
See 2 more Smart Citations
“…Hay antecedentes de estudios previos que apoyan el planteamiento de las hipótesis 6.1 y 7.0 (Antón, Camarero & San José, 2013; M.-C. Weng & Tsai, 2015), por ello fueron evaluadas en esta investigación. Estos estudios sostienen que la satisfacción de un usuario respecto a una tecnología específica se ve influenciada por la utilidad percibida y a su vez la satisfacción influye directamente en el uso de la misma.…”
Section: H70 La Satisfacción Tiene Un Impacto Positivo En El Uso Deunclassified